The Process of Recognizing Indigenous Communities and Establishing Customary Forests in North Tapanuli - Tambunan, Rytha (RSF Conference Series: Business, Management and Social Sciences, 2023)
Indigenous people are communally entitled to customary forests and are referred to as having customary rights. There are structural inequalities and the distribution of land that the government hands over to large corporations rather than to Indigenous People. This study focused on (1) How is the process of recognizing customary law communities and establishing customary forests in the Toba Batak community in the North Tapanuli Regency after the Constitutional Court's decision Number 35/PUU-IX/2012 and how the interactions of various regulations implemented? (2) How do regulations interact when they are used as the basis for recognizing indigenous people and establishing their customary forests? (3) Why are customary rules and state policies still used in the process of resolving forest claim conflicts in issuing decrees for establishing customary forests? This research was conducted by collecting data through field observations, in-depth interviews, and gathering relevant data and documents. This study is expected to provide a better understanding of the process of customary identification and the establishment of customary forests in North Tapanuli, as well as provide input to the government and relevant stakeholders to enhance the protection and sustainability of customary rights and the management of customary forests in the region.